Explaining the Success of the World's Leading Education Systems: The Case of Singapore. Issue 2 (2nd April 2016) - Dimmock, Clive; Tan, Cheng Yong
ABSTRACT: International comparative data on student performance has led McKinsey&Company, among others, to suggest that education systems will inexorably converge in their developmental trajectories with principals and schools enjoying more autonomy. This article challenges these assumptions through referencing Singapore where schools and professionals are still tightly controlled in key resources, curricula and assessment, and where other key factors contribute to its success – thereby evidencing multiple pathways to success.